The role of women in security Indonesian women peacekeepers in the UNIFIL: Challenges and opportunities - Rany Purnama Hadi; Sartika Soesilowati (Masyarakat, Kebudayaan dan Politik, 2018)
Following Security Council Resolution 1325 (2000), the United Nations arranged mandates on women, peace and security (WPS) in order to address the equality between men and women, in order to allow them to actively participate in managing world security and peace. The purpose of this mandate was to give women the same opportunities, protection, access to resources and services, as well as right to participation in decision-making, as an attempt to achieve and sustain peace and security. In 2014, women constituted 3% of the UN’s military personnel and 10% of the police personnel out of the total number of UN peacekeepers from 123 countries, including Indonesia. In Lebanon, one of the areas focused on by UN peacekeeping missions, Indonesia currently deploys the largest peacekeeping personnel of up to 1,296 individuals, of which 24 are women. This number constitutes 5% of Indonesia’s total peacekeepers on the UN’s mission. Using the qualitative approach method through collecting secondary data, this paper aims to examine the participation of Indonesian women peacekeepers, particularly in UNIFIL, in relation to helping, protecting and supporting women and girls as the victims of war based on the feminist point of view. It was found that Indonesian women peacekeepers provide a tremendous contribution to the eﬀectiveness of the UN’s peacekeeping operations. Women can provide softer approaches toward war victims and help to promote peace in the region. This shows that women still have not had much opportunity to prove their abilities in battle. Therefore, improvement is needed in order to increase the Indonesian women’s peacekeeper role in peacekeeping operations.